Commercial banks, default insurance and IMF reforms - Duane W. Rockerbie; Stephen T. Easton (Kiel Institute for the World Economy (IfW), 2009)
This paper discusses, in a very general way, a system of IMF insurance against sovereign default that could be offered to private lenders and banking groups. The system could overcome many of the current issues that plague the international private lending market, such as moral hazard on the part of private lenders, capital flight, and so on. How the insurance could be priced is also discussed in an appendix. Private lender membership in the IMF is also discussed. This would provide the IMF with some of the powers that central banks now have.
Keywords: F33; F34; Sovereign debt; insurance; option value; IMF